PENGARUH KUALITAS PRODUK, CITRA MEREK, DAN PERSEPSI HARGA TERHADAP KEPUTUSAN PEMBELIAN SEPATU ADIDAS DI D.I.YOGYAKARTA - Elvina, Bella (PERFORMA, 2022)
In this pandemic period, more people who concern about health, to maintain health, healthy lifestyle is needed, one of them is by exercising. A lot of people start living healthier like jogging, cycling, and others. This thing is in accordance with the increasing demand of athletic shoes, market demand for athletic shoes is also increased as 50% during Large-scale Social Restriction, before buying a product, consumers also will consider first, such as comparing one product with another product, seeking information about the product, and so on. The purpose of this research is to find out the effect of product quality, brand image, and price perception on purchase decision of Adidas shoes at D.I. Yogyakarta. Z generation is the generation that was born from 1997 to 2012. Z generation is the generation that has been able to make own decision in terms of clothing, including in terms of making purchase decision. This research uses causal by using the sample of z generation respondents in Yogyakarta that have done purchase of Adidas shoes, from 167 respondents, 56% of them are men and 44% of them are women. This research is quantitative and uses Likert scale which is then processed using SPSS 26. The result of this research indicates that men are more interested in Adidas shoes compared to women, then product quality and price perception affect simultaneously on purchase decision of Adidas shoes in Yogyakarta, while brand image variable does not have effect on purchase decision of Adidas shoes in Yogyakarta. The three independent variables that are analyzed have the most effect on dependent variable are price perception variable on Adidas shoes, then purchase decision is affected by the quality of Adidas shoes products